MODEST EFFECT OF HIGH SALT DIET ON INFLAMMATORY BIOMARKERS IN SPRAGUE-DAWLEY RATS. (June 2018) - Drenjancevic, I.; Matic, A.; Mihaljevic, Z.; Bilic-Dujmusic, N.; Stupin, A.
Abstract : Objective: A number of recent studies emphasize low-grade vascular inflammation as important pathophysiological mechanism underlying endothelial dysfunction in hypertension. Since high dietary salt intake is known causal factor of endothelial dysfunction even without increases in arterial blood pressure, the aim of this study was to assess the effect of 7-days high salt intake on serum proinflammatory cytokines' levels and their genes expression in cerebral blood vessels of normotensive Sprague-Dawley rats. Design and method: 11-weeks old healthy male rats (N = 7–10/per group) were divided in two groups: low salt (LS) group fed 0.4% NaCl chow and HS group fed 4% NaCl chow for 1 week. After dietary protocol rats were anesthetized with ketamin-chloride (75 mg/kg) and midazolam (2.5 mg/kg), blood pressure measured with intraarrterial catheterization and rats were sacrificed. Serum samples for ELISA and all surface cerebral blood vessels for mRNA gene expression analysis of TNF-α, IL-1, IL-6, GRO-alpha, ICAM-1, VCAM-1 and MCP by real-time quantitative PCR (rtPCR; BioRad CFX96) were collected and analyzed by Student t-test. p < 0.05 was considered significant. All experimental procedures conformed to the European Guidelines for the Care and Use of Laboratory Animals (directive 86/609) and were approved by the local Ethical Committee. Results: Serum level of TNF- α was significantly increased after high salt diet (p = 0.021) without significant changes of other parameters. Gene expression of investigated genes in cerebral blood vessels was not significantly changed (p > 0.05). Conclusions: The results of the present study demonstrated that 7-days HS diet only modestly influences cytokine production in cerebral blood vessels.